Technology assessment of cyber security in the Philippine Banking Industry - Ambrocio, Deah S.; Cruz, Edison D. (Quezon City University of the Philippines Diliman, 2017)
The concept of cyber security in the Philippine Banking Industry took place when the banks started to drift away from traditional banking to digital banking. Digital banking refers to the usage of online and mobile platforms in offering banking products and services to the customers. The extensive use of technology by the Philippine banks resulted for them to be more exposed in the cyber space, hence in the cyber threats as well.
Cyber security is now then considered as a crucial factor in the business growth of Philippine banks as each technology they use for profits needs protection from technology that will cause destruction to these income generating technologies. Philippine Banking Industry realized this matter and has slowly built their own cyber security framework for their own protection. However, it is obvious that Philippines is one step behind when it comes to technology compared with other countries, and this affected the banking industry making it more prone to cyber threats and attacks. Having said this, the central bank, the government and the local banks are individually challenging themselves in developing cyber security techniques and strategies to combat cyber threats and attacks.
This project report was conducted to provide an assessment of the current state of cyber security in the Philippine Banking Industry through comparing the cyber security guidelines of the country's central bank with other two Asian countries, evaluating the cyber security framework of a local bank and providing forecasted scenarios to predict the future of cyber security in the Philippine Banking Industry. Through the assessment, recommendations are formulated which mainly focuses on having a stronger communication among the Philippine banks, the central bank and the government so that the current state of cyber security in the banking industry will be more resilient and robust.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Technology assessment; Computer security; Banks and banking -- Philippines